2018
DOI: 10.4067/s0718-58392018000400521
|View full text |Cite
|
Sign up to set email alerts
|

Association between arbuscular mycorrhizal fungi and Pratylenchus brachyurus in maize crop

Abstract: Maize (Zea mays L.) is one crop of major relevance in Brazil; however, nematodes are limiting factors in maize growth and productivity due to the difficulty to control them. Studies point out that arbuscular mycorrhizal fungi (AMF) increase plant tolerance to nematodes. Thus, the aim of this study was to assess the association between AMFs and Pratylenchus brachyurus in maize growth. Six AMF species (Rhizophagus clarus, Claroideoglomus etunicatum, Gigaspora rosea, G. margarita, Scutellospora calospora, S. hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Tolerance conferred by AMF to a crop under Pratylenchus pressure has been described in the majority of the reviewed papers ( n = 41) with the exception of the following; peach, Musa sp., maize, tomato, dune grass and wheat (Pinochet et al, 1995b ; Elsen et al, 2003a ; Rodríguez-Echeverría et al, 2009 ; Vos et al, 2012 ; Brito et al, 2018 ; Frew et al, 2018 ). This may be a reflection of the mycorrhizal dependency of the cultivars assessed as some tomato and wheat cultivars have a low mycorrhizal dependency (Smith et al, 2009 ) while cultivars of maize, Musa sp.…”
Section: Discussionmentioning
confidence: 99%
“…Tolerance conferred by AMF to a crop under Pratylenchus pressure has been described in the majority of the reviewed papers ( n = 41) with the exception of the following; peach, Musa sp., maize, tomato, dune grass and wheat (Pinochet et al, 1995b ; Elsen et al, 2003a ; Rodríguez-Echeverría et al, 2009 ; Vos et al, 2012 ; Brito et al, 2018 ; Frew et al, 2018 ). This may be a reflection of the mycorrhizal dependency of the cultivars assessed as some tomato and wheat cultivars have a low mycorrhizal dependency (Smith et al, 2009 ) while cultivars of maize, Musa sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed these mechanisms, for example, mycorrhizas (Rhizophagus intraradices and Funneliformis mosseae) reduce tomato root penetration by false root-knot nematode Nacobbus aberrans (Marro et al, 2018), in the same way as the application of Glomus intraradices, G. mosseae, and G. etunicatum against M. javanica in peach trees (Calvet et al, 2001). In contrast, the increment in root colonization by mycorrhizae (Rhizophagus clarus, Claroideoglomus etunicatum, Gigaspora rosea, G. margarita, Scutellospora calospora, and S. heterogama) caused an increase in the population of nematodes Pratylenchus brachyurus in maize crop (Brito et al, 2018) which is opposite to the effect in cotton (Ferreira et al, 2018). All these mechanisms and their effectiveness on the populations and the capacity of infection of the phytoparasitic nematodes will depend closely on the local environmental conditions.…”
Section: Mycorrhizal Fungimentioning
confidence: 95%
“…Nutrient uptake (p) Increased -N; P; K; Ca; Mg; Na [37,186,[207][208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223] Nutrient uptake (f) Increased -P; K; Ca; Mg; Fe [221,[224][225][226] Vegetative growth (p) Increased -shoot and root biomass; root length; plant, leaf and tassel length; stem girth [186, 203, 205, 206-209, 211, 213, 214, 216, 219, 221-229] Vegetative growth (f) Increased -shoot and root biomass; root length; plant height; leaf mass and area [217,221,224,226,[230][231][232][233][234] Yield (p) Increased -cob and grain yield; number of grains per cob [215,221,[235][236][237] Yield [86,266], while for glomalin, it varies from 6 to 42 years [120]. The effects of AM fungi on soil aggregation are probably more easily detected in nutrient-poor soils with neutral or alkaline soil pH [268].…”
Section: Parameter (P/f) * Benefits Referencementioning
confidence: 99%